Globalization and Growth - Implications for a Post-Crisis World : Commission on Growth and Development - Spence, Michael; Leipziger, Danny (World Bank, 2012)
The commission on growth and development was established in April 2006 as a response to two observations. While the author felt that the benefits of growth were not fully appreciated, the author recognized that the causes of growth were not fully understood. Growth is often overlooked and underrated as an instrument for tackling the world's most pressing problems, such as poverty, illiteracy, income inequality, unemployment, and pollution. At the same time, understanding of economic growth is less definitive than commonly thought, even though advice sometimes has been given to developing countries with greater confidence than perhaps the state of our knowledge will justify. Consequently, the commission's mandate was to 'take stock of the state of theoretical and empirical knowledge on economic growth with a view to drawing implications for policy for the current and next generation of policy makers.' This mandate has even more significance in the aftermath of the financial and economic crisis of 2008. As developing countries seek to repair the damage to their economies and to re-launch themselves on a sustained high-growth path, there has never been a greater need for fresh new ideas and approaches to achieving sustained high growth. There has been no dearth of commentary about what the crisis may mean, but in reality, until the bottom has been reached and the path to recovery is clear, it will be difficult to draw general lessons for the future. This collection of essays encompasses a variety of viewpoints and covers both medium- and long-term policy issues. It is said that more textbooks have become obsolete in 2009 than in any year since the great depression. As a corollary, much has been written that is worth reviewing in a volume on globalization. The papers look at the issue of globalization from diverse points of view and add insights and perspective to the recommendations of the growth report.